P-ranks and automorphism of group divisible designs. - Tan, Yee Sern. (2009)
Group Divisible Designs are studied with their corresponding Relative Dif- ference Sets using methods of vector spaces, nite elds, classical geometries, group rings, and complex characters. Examples of Group Divisible designs are given with their Singer groups and class regular subgroups. The correspondence of semiregular Group Divisible Designs with symmetric nets and also with generalised Hadamard matrices are shown.